Britain in the Middle East 1619-1971 - Harrison, Robert T. (Bloomsbury Academic, 2016)
Britain in the Middle East provides a comprehensive survey of British involvement in the Middle East, exploring their mutual construction and influence across the entire historical sweep of their relationship. Robert Harrison charts this relationship, exploring how the Middle East served as the launchpad for British offensive action in the World Wars, and how resentment against colonial rule in the region led ultimately to political and Islamic revolutions and Britain's demise as a global, imperial power.